Hepatocellular adenoma and focal nodular hyperplasia of the liver: differential diagnosis in dogs - Xavier, José Guilherme; Dagli, Maria Lucia Zaidan; Vianna, Maria Regina; Malucelli, Benjamin Eurico (Brazilian Journal of Veterinary Research and Animal Science, 1992)
Among the hepatic lesions routinely foind in veterinary necropsy practice, nodular lesions are the less described. These lesions include both reactive or neoplastic processes and hamartomas. This study was performed in order to differentiate the hepatocellular adenomas (HA) from the hepatic focal nodular hyperplasia (FNH) in dogs. Ten cases of nodular hepatic lesions in dogs were surveyed from the archives of the Department of Pathology of the “Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo". To each case, histochemical and immuiohistochemical methods were applied in order to characterize the lesions, according to histological human predefined criteria. From the results recorded it was possible to diagnose eight cases of FNH and two cases of HA. It was concluded that these techniques can be easily performed and are suitable for the proposed objectives.